Penyusunan Modul Training 7 QC Tools dan Project Management untuk Mendukung Program Continuous Improvement di PT. X - Yobel Manuel; Herri Christian Palit (Jurnal Titra, 2022)
PT. X is a cigarette company that applies the principle of Continuous Improvement. The Continuous Improvement Program has been implemented in one of the departments in the HRD Division, namely the HR Project. The program is still not running optimally due to a lack of understanding from the employees of PT. X deals with analytical tools for quality control as well as project management. The solution given to overcome the problem is to prepare training modules from 7 QC Tools and Project Management which are made simple and attractive so that they are easy to understand. The Project HR Supervisor has tested the module through trial and inspection activities. The HR Project and the Training Team have evaluated by comparing the old and new modules. The overall average for the old module is 2.08, and the new module is 3.50. The 7 QC Tools training module is also implemented in one of the programs, namely HR Survey 2021 on Suggestion Comment data processing using Pareto Diagrams.